Dispersed hydroxyapatite bioglass 45S5 composites: Comparative evaluation of the use of bovine bone and synthetic hydroxyapatite - Silva, A. C.; Aparecida, A. H. [UNESP]; Braga, F. J C (Trans Tech Publications, 2012)
The bovine bone and sintetic hydroxyapatite (HA) bioceramics are reference materials to employment as a bone substitute, however, their slow rate of degradation and its low rate of bioactivity index (Ib) are presented as limiting factors for application as bone graft. In contrast, the bioglass is a resorbable and osteoinductive material. the present work objective the development of composites of dispersed bovine bone or sintetic HA in silicate-phosphate bioglass, seeking to obtain a biomaterial with properties suitable for application as bone grafts. The composites were prepared by mixing between the powder components followed by sintering for 1h. Were used HA and bioglass (45S5) with particle size <240μm. The tested proportions of HA/45S5 were 20/80, 30/70 and 40/60 (wt%). The composites characterization was made employing scanning electron microscopy, Infra-Red Spectrometry and hydrolytic resistance test. The test results indicate the potential use of the materials developed for applications such as bone graft. © (2012) Trans Tech Publications, Switzerland.
Keywords: Bioglass; Biomaterials for bone replacement; Hydroxyapatite; Bone graft; Bone replacement; Bone substitutes; Bovine bone; Comparative evaluations; Hydrolytic resistance; Low rates; Reference material; Resorbable; Synthetic hydroxyapatite; Bioactive glass; Bioceramics; Biological materials; Characterization; Grafting (chemical); Infrared spectroscopy; Mammals; Scanning electron microscopy; Silicates; Sintering; Bone